SURTO DE ð˜›ð˜©ð˜ºð˜³ð˜ªð˜¯ð˜µð˜¦ð˜ªð˜¯ð˜¢ ð˜¢ð˜³ð˜¯ð˜°ð˜£ð˜ªð˜¢ (STOLL, 1782) (LEPIDOPTERA, GEOMETRIDAE) EM ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ ð˜¤ð˜ªð˜µð˜³ð˜ªð˜°ð˜¥ð˜°ð˜³ð˜¢ HOOK. (MYRTACEAE) NO ESTADO DE SÃƒO PAULO - Berti Filho, E.; Stape, J. L.; Cerignoni, J. A. (REVISTA DE AGRICULTURA, 2020)
SURTO DE ð˜›ð˜©ð˜ºð˜³ð˜ªð˜¯ð˜µð˜¦ð˜ªð˜¯ð˜¢ ð˜¢ð˜³ð˜¯ð˜°ð˜£ð˜ªð˜¢ (STOLL, 1782) (LEPIDOPTERA, GEOMETRIDAE) EM ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ ð˜¤ð˜ªð˜µð˜³ð˜ªð˜°ð˜¥ð˜°ð˜³ð˜¢ HOOK. (MYRTACEAE) NO ESTADO DE SÃƒO PAULO Â 